Kafala and adoption. The resolution of the Provincial Court of Barcelona (Section 18) number 220/2020 10 June - Adroher Biosca, Salomé (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
Adopting a child in Spain after a kafalah in his country of origin, is forbidden under spanish law since 2015, as in other european countries. Nowadays, some muslim migrant families try to adopt to avoid some immigration barriers. The case shows that the prohibition is consistent with the best interest of the child, already protected by the kafalah, but also that immigration laws must guaranty his right to a effective family life.